CONTEMPORARY UNDERSTANDING THE STATE SOVEREIGNTY IN EUROPEAN UNION INTEGRATION DISCOURSE - Майніна, М. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
After the treaty of the European Union was signed, the problem of preserving state sovereignty by the members of the association has become more acute. For a long period, debate over the issue of the correlation of sovereignty and integration continued among the scientists. Now, this question is faced by countries which are planning to become a part of European integration. This article is devoted to the consideration of the peculiarities of the transformation of state sovereignty under the influence of integration processes. Author analyzed several concepts of determining the place of state sovereignty in the integration discourse of the European Union. The following concepts have been identified within the research: pooled sovereignty, shared sovereignty, limited sovereignty, late sovereignty, post-sovereignty, (cooperative sovereignty, mixed sovereignty, etc. Based on the research results, the development of state sovereignty is defined: 1. absolutist-unitaristic; 2.disaggregation and reaggregation of sovereignty 3. post-sovereignism and 4.cooperative.Paying attention to this fact, the significance of state sovereignty in the modern world can be considered from two positions: territorial and functional. It is possible to state the principal changes of the approaches to its definition. The emergence of new approaches to the definition of state sovereignty is connected with the fact that scientists interpret the functional side of state sovereignty in a number of different ways.Although, each theory has a unique approach to explaining the process of interaction between states within the European integration process, they have a common feature that concerns the functional boundaries of state sovereignty. This makes it possible to confirm the thesis that the process of European integration cannot destroy the sovereignty of a state. There is an expansion of the state’s functional capabilities in some areas. State sovereignty remains a constant category. The change relates to the order of interaction of states in the international arena, and therefore partly applies to the issue of the functional side of sovereignty.